Metabolic Inflexibility Is an Early Marker of Bed-Rest–Induced Glucose Intolerance Even When Fat Mass Is Stable - Rudwill, Floriane; O’Gorman, Donal; Lefai, Etienne; Chery, Isabelle; Zahariev, Alexandre; Normand, Sylvie; Pagano, Allan F; Chopard, Angèle; Damiot, Anthony; Laurens, Claire; Hodson, Leanne; Canet-Soulas, Emmanuelle; et al. (The journal of clinical endocrinology and metabolism, 2018)
Abstract Context The effects of energy-balanced bed rest on metabolic flexibility have not been thoroughly examined. Objective We investigated the effects of 21 days of bed rest, with and without whey protein supplementation, on metabolic flexibility while maintaining energy balance. We hypothesized that protein supplementation mitigates metabolic inflexibility by preventing muscle atrophy. Design and Setting Randomized crossover longitudinal study conducted at the German Aerospace Center, Cologne, Germany. Participants and Interventions Ten healthy men were randomly assigned to dietary countermeasure or isocaloric control diet during a 21-day bed rest. Outcome Measures Before and at the end of the bed rest, metabolic flexibility was assessed during a meal test. Secondary outcomes were glucose tolerance by oral glucose tolerance test, body composition by dual energy X-ray absorptiometry, ectopic fat storage by magnetic resonance imaging, and inflammation and oxidative stress markers. Results Bed rest decreased the ability to switch from fat to carbohydrate oxidation when transitioning from fasted to fed states (i.e., metabolic inflexibility), antioxidant capacity, fat-free mass (FFM), and muscle insulin sensitivity along with greater fat deposition in muscle (P < 0.05 for all). Changes in fasting insulin and inflammation were not observed. However, glucose tolerance was reduced during acute overfeeding. Protein supplementation did not prevent FFM loss and metabolic alterations. Conclusions Physical inactivity triggers metabolic inflexibility, even when energy balance is maintained. Although reduced insulin sensitivity and increased fat deposition were observed at the muscle level, systemic glucose intolerance was detected only in response to a moderately high-fat meal. This finding supports the role of physical inactivity in metabolic inflexibility and suggests that metabolic inflexibility precedes systemic glucose intolerance. Bed-rest–induced physical inactivity triggers metabolic inflexibility, which can be used as an early marker of metabolic disturbances developed in response to the adoption of sedentary behaviors.